Kinetics of Muscle Damage Biomarkers at Moments Subsequent to a Fight in Brazilian Jiu-Jitsu Practice by Disabled Athletes - Santos Silva Lopes, Jaqueline; Monteiro de Magalhães Neto, Aníbal; Oliveira Gonçalves, Luís Carlos; Lourenço Alves, Paulo Ricardo; Castilho de Almeida, Aline; Marlise Balbinotti Andrade, Claudia (Frontiers in Physiology, 2019)
Purpose: Evidence indicates that muscle injury caused by exercise can lead to functional, biochemical, and clinical damage. These outcomes encompass an intrinsic potential to understand the real magnitude of interpretation of classic signs in sport environments and to monitor athletes, contributing to specific actions. However, little or no research has explored the general behavior of the variables presented in response to para jiu-jitsu. The objective of this study was to investigate the physiological behavior through clinical, functional, and metabolic outcomes in the moments following a simulated fight. Methods: Six male para jiu-jitsu practitioners (34-44 years old) were included. Participants were allocated to two groups, G1 (consisting of high-performance parathletes) and G2 (consisting of amateur-level parathletes). The study was accepted by the ethics committee involving human beings of the Federal University of Mato Grosso (opinion no. 2.997.241) and duly registered in clinical trials.gov (NCT03698578). The participants attended the collection site 4 times, with a 24-hour interval between sessions, characterizing the following moments: pre-exertion, and post-exertion, 24, 48, and 72 hours after the simulated fight. Data were collected on muscle pain, perception of recovery, muscle strength, and blood samples for CK and LDH analysis. The variables described were measured at all collection moments. The data were analyzed by means of Variance Analysis of Repeated Measures (ANOVA), with a significance level of 5% (p <0.05). Results: The outcomes demonstrated that the CK and LDH activity in the group composed of high-performance parathletes was higher and the reported muscle pain was lower. The fight did not influence maximal isometric strength levels in either group. In addition, regarding delayed effects, both groups reported peak pain, CK, LDH, and decreased perception of recovery within 24 hours. However, it was found that, at 72 hours, all values had recovered, close to baseline levels. Conclusion: The presented outcomes provide parameters and suggest a safe scenario based on the intensity and volume commonly adopted in this parasport modality where the level of effort recommended during combat does not seem to cause delayed damage.